2013
DOI: 10.2528/pier13041207
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Taylor-Based Worst-Case Model for Field-to-Line Coupling

Abstract: Abstract-To obtain Electromagnetic Compatibility (EMC), we would like to study the worst-case electromagnetic field-induced voltages at the ends of Printed Circuit Board (PCB) traces. With increasing frequencies, modelling these traces as electrically short no longer suffices. Accurate long line models exist, but are too complicated to easily induce the worst case. Therefore, we need a simple analytical model. In this article, we predict the terminal voltages of an electrically long, two-wire transmission line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…As anything can be modeled in a full-wave solver, only the validity constraints of modified Taylor cells need to be considered. The modified Taylor cell predicts the coupling of a grazing, horizontally polarized plane wave to one straight, characteristic microstrip segment [5]. If the impedance discontinuities between segments are negligible, a finite cascade of microstrip segments of different planar orientation can be modeled by cascading Taylor cells [6].…”
Section: Case Study:ameanderedshorted Microstripmentioning
confidence: 99%
See 2 more Smart Citations
“…As anything can be modeled in a full-wave solver, only the validity constraints of modified Taylor cells need to be considered. The modified Taylor cell predicts the coupling of a grazing, horizontally polarized plane wave to one straight, characteristic microstrip segment [5]. If the impedance discontinuities between segments are negligible, a finite cascade of microstrip segments of different planar orientation can be modeled by cascading Taylor cells [6].…”
Section: Case Study:ameanderedshorted Microstripmentioning
confidence: 99%
“…Given the available surface, a threesegment microstrip is chosen for simplicity's sake. Because the far end has the stronger high-frequency coupling for a straight microstrip [5], the far-end induced voltage is studied. At the near end, a short calibration standard is connected, inevitably including an electrical delay ⌧ d .…”
Section: Case Study:ameanderedshorted Microstripmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective PME is the result of HPM coupling onto printed circuit board (PCB) traces (back door coupling) [13]. It is observed that a MOS inverter that initially follows the interference may switch to a state where it is totally inhibited and pinned down to the lower logic level.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, Op 't Land et al proposed a model for the coupling of a plane wave to a PCB (Printed Circuit Board) trace [1]. To challenge the model, they confronted it to measurements where the GTEM cell was used to emulate the plane wave.…”
Section: Introductionmentioning
confidence: 99%